2003
DOI: 10.1128/jvi.77.22.11910-11917.2003
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Human Hepatitis Delta Virus RNAs to Dicer Activity

Abstract: The endonuclease dicer cleaves RNAs that are 100% double stranded and certain RNAs with extensive but <100% pairing to release ϳ21-nucleotide (nt) fragments. Circular 1,679-nt genomic and antigenomic RNAs of human hepatitis delta virus (HDV) can fold into a rod-like structure with 74% pairing. However, during HDV replication in hepatocytes of human, woodchuck, and mouse origin, no ϳ21-nt RNAs were detected. Likewise, in vitro, purified recombinant dicer gave <0.2% cleavage of unit-length HDV RNAs. Similarly, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 55 publications
(54 reference statements)
2
35
0
5
Order By: Relevance
“…Thus, there is a solid basis for a structured PSTVd RNA to serve as a DCL substrate in vivo. It should be noted that a previous study showed that the plus-PSTVd RNA was resistant to cleavage by human dicer (15). Whether this is attributed to some differences in the biochemical activities of human and plant dicers or in technical procedures is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, there is a solid basis for a structured PSTVd RNA to serve as a DCL substrate in vivo. It should be noted that a previous study showed that the plus-PSTVd RNA was resistant to cleavage by human dicer (15). Whether this is attributed to some differences in the biochemical activities of human and plant dicers or in technical procedures is unknown.…”
Section: Discussionmentioning
confidence: 98%
“…The hepatitis delta virus genome is largely but not completely duplex RNA. While it can be edited in a site-selective manner by ADAR and can activate PKR (48, 313), it cannot be cleaved by Dicer (43). On the other hand, fragile X syndrome transcripts encode trinucleotide repeats that can form RNA hairpins that cannot activate PKR but are efficiently cut by Dicer (122).…”
Section: Vol 68 2004mentioning
confidence: 99%
“…This would be sufficient to protect them against cleavage by Dicer, which requires a minimum of Ϸ19 bp of dsRNA (46). Several recent observations support a direct role of secondary RNA structures in conferring resistance to RNA silencing: (i) regions of a plant mRNA that have the potential to form duplex structure have been shown to accumulate in cells where the mRNA is silenced (47), (ii) a short defective interfering viral RNA, with the potential to form a stable secondary structure, is significantly more resistant to RNA silencing than is its helper virus (48), and (iii) PSTVd or viroid-like RNAs are highly resistant to Dicer cleavage in an in vitro system (49).…”
Section: Does Rna Silencing Mediate the Evolution Of Viroids And Viralmentioning
confidence: 99%